The problem of reforming the ‘National Security’ branch of science - Krutov, V. V.; Kyrychenko І. О. (Honor and Law, 2019)
The appropriateness to include the National security science branches in the List of the branches of science in which scientific degrees and academic ranks are awarded is substantiated.